Cognitive Mechanism of Emotional Validity Influencing Conflict Control - Zhi Zhu; Wei Xu; Song Xue (International Journal of Psychotherapy Practice and Research, 2019)
Conflict control is the ability to choose relevant information and ignore disturbing information in task processing. Previous studies have found that emotions have a certain influence on conflict control, and the research results of positive emotions and negative emotions affect conflict control are inconsistent. This study attempted to explore the effects of different emotional valorization on conflict control, using images of happy, fearful and sad emotional faces to investigate the effects of different emotional valorization and different emotional types on conflict control. The experiment selected 40 participants and used the variable-face Stroop paradigm. The study found that no matter what emotional task, there is a significant conflict effect. The effects of different valency on conflict control are different. All three emotions have a significant effect on conflict control, and positive emotions play a role in promoting conflict control.
Keywords: Conflict Control